Procalcitonin and C-reactive protein levels in HIV-positive subjects with tuberculosis and pneumonia - G. Schleicher; Victor Herbert; Adrian Brink; Seán Martin; Rajiv Maraj; Jacqueline S. Galpin; Charles Feldman (2005)
Pulmonary tuberculosis (PTB) and pneumococcal community-acquired pneumonia (PCAP) are common causes of lower respiratory tract infections in HIV-seropositive patients and may have similar clinical and radiological features. This study aimed to assess the value of serum procalcitonin (PCT) and C-reactive protein (CRP) levels in HIV-seropositive patients with pneumonia, and to investigate their potential role in differentiating pneumococcal from mycobacterial infections. HIV-seropositive patients admitted with pneumonia were evaluated prospectively, 34 with PTB and 33 with PCAP. All 33 patients in the PCAP group and 20 of 34 patients in the PTB group had elevated PCT levels (>0.1 ng x mL(-1)). All patients in both groups had elevated CRP levels (>10 mg x L(-1)). The PTB group had significantly lower CD4 T-lymphocyte counts, lower CRP levels, lower white cell counts, and lower PCT levels than the PCAP group. Receiver operating characteristic analysis showed that optimal discrimination between PTB and PCAP could be performed at a cut-off point of 3 ng x mL(-1) for PCT (sensitivity 81.8%; specificity 82.35%) and 246 mg x L(-1) for CRP (sensitivity 78.8%; specificity 82.3%). In conclusion, HIV-seropositive patients with pneumococcal community-acquired pneumonia had significantly higher procalcitonin and C-reactive protein levels than those with pulmonary tuberculosis. A procalcitonin level >3 ng x mL(-1) and a C-reactive protein level >246 mg x L(-1) were both highly predictive of pneumococcal infection.